ASSESSMENT OF MUSCLE LONGISSIMUS THORACIS ET LUMBORUM INTRAMUSCULAR FAT BY ULTRASONOGRAPHY AND IMAGE ANALYSIS - Silva, Severiano; Patricio, Marcia; Guedes, Cristina; Mena, Elisabete; Silva, Antonio; Santos, Virginia; Jorge, Andre [UNESP]; Cadavez, V; Thiel, D. (Eurosis, 2010)
The intramuscular fat (IMF), recognized by the consumer as marbling, has a favorable effect on meat quality and therefore is an important trait to be assessed. The objective of this work is to predict Longissimus thoracis et lumborum muscle (LM) chemical IMF from marbling traits obtained by analysis of real time ultrasonography (RTU) images. Twenty six LM samples were collected from Charolais x Holstein heifers. The RTU images were obtained from LM samples using a RTU scanner equipped with a 7.5 MHz probe. The chemical fat of IMF was determined on LM. samples. The RTU images were subjected to computer image analysis to determine the characteristics of marbling flecks. Simple and multiple regressions were established between the chemical IMF (Y) and the characteristics of marbling flecks determined by RTU (X). Stepwise procedures were used to found the best fit model to predict chemical IMF. A large variation was found for the characteristics of marbling flecks. Using regression analysis it was possible to predict chemical IMF from marbling fleck area and proportion of marbling flecks (R-2=0.66 and 0.82, respectively, P<0.0001). The best fit explains 85% of chemical IMF variation. The results observed in this work suggest that RTU associated with image analysis was a valuable tool to predict chemical IMF of LM without destroying the muscle chop.
Keywords: Intramuscular fat; ultrasound; image analysis